Analysis of the Need for the Development of E-Module Teaching Materials Integrated Local Wisdom Culture Based on Project Based Learning (PjBL) on Reaction Rate Material - Citra Sianturi; Silaban , Ramlan; Edwin Pakpahan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to analyze the need for improvement of chemistry teaching materials for high school grade XI on reaction rate material, and the findings of this study will be consulted for further information in the development of electronic chemistry teaching materials or e-modules that are integrated with project-based learning-based ethnopedagogy. A qualitative descriptive method was employed in this study. The research was conducted at SMAN 2 Percut Sei Tuan through interviews with a chemistry teacher and classroom observations in class XI-C, involving 36 students. The results indicate that the teacher has never used e-modules in chemistry learning, particularly for reaction rate materials. Learning activities are still limited due to the lack of laboratory tools and materials, resulting in the use of simple teaching resources that are not integrated with local wisdom. The teacher also acknowledged that the development of ethnopedagogy-based e-modules integrating local wisdom is highly necessary to provide authentic learning experiences, enabling students to better understand abstract reaction rate concepts and construct their own understanding independently. Furthermore, the results of the student needs analysis questionnaire show that 85.5% of students are interested in and agree with the development of project-based e-modules integrated with ethnopedagogy, as this approach supports independent exploration of their understanding.